IMPROVEMENT OF BOARDWALK NAILED – SPAN BRIDGE STRUCTURES - V. A. Utkin; P. N. Kobzev (Вестник СибАДИ)
The article is devoted to the implementation in practice of the construction of the new bridge boardwalk timber - nail span structures that meet the modern requirements of load capacity, reliability and durability. The authors propose and describe a new design of the span timber-beam-peg–nailed blocks with longitudinal-transverse orientation of the belt boards and carrying transverse reinforced concrete slab of the carriageway. The represented materials show the effectiveness of the proposed solutions.